Profiles of Stress and Coping Associated With Mental, Behavioral, and Internet Use Problems Among Adolescents During the COVID-19 Pandemic: A Stratified Random Sampling and Cluster Analysis - She, Rui; Wong, Keiman; Lin, Jiaxi; Zhang, Youmin; Leung, Kinlong; Yang, Xue (Frontiers in Public Health, 2022)
Background Adolescents are vulnerable to behavioral and mental health problems, which might be further exacerbated during the COVID-19 pandemic. This study explored how participants with different profiles of stressful life events, coping resources (i.e., self-esteem and perceived social support) and coping strategies (i.e., maladaptive and adaptive coping) varied in the prevalence of mental, behavioral, and Internet use problems. Methods Data were collected from a large and representative sample of Chinese secondary school students in Hong Kong (n = 3,136) from September to November 2020 (48.1% males; mean age = 13.6 years old). Cluster analysis and logistic regression models were used for analysis. Results The prevalence of suicidal ideation and sleep disturbance was 29.8 and 55.4%, respectively. Behavioral problems were most frequently reported in excessive social media use (53.5%), followed by excessive Internet gaming (43.6%), obesity (34.1%), damaging properties (14.6%), and alcohol or substance abuse (5.1%). The results of cluster analysis yielded three distinctive stress and coping profiles: severe profile (High Risk/Low Protective; 17.0%), moderate profile (Moderate Risk/Moderate Protective; 35.8%), and mild profile (Low Risk/High Protective; 47.2%). Participants with severe and moderate profiles displayed significantly higher levels of mental (range for AOR: 2.08–15.06; all p < 0.001) and behavioral health problems (range for AOR: 1.22–11.22; all p < 0.05) compared to the mild profile cluster. Conclusions Adolescents' mental and behavioral health may be shaped by a combination of stressful life events and variations in coping resources as well as strategies. Transdiagnostic and multimodal interventions on these factors are warranted to reduce mental, behavioral, and Internet use problems among adolescents.